Sisyphus's boulder : consciousness and the limits of the knowable - Dietrich, Eric (Advances in consciousness research, 2005)
Consciousness lies at the core of being human. Therefore, to understand ourselves, we need a theory of consciousness. In Sisyphus's Boulder, Eric Dietrich and Valerie Hardcastle argue that we will never get such a theory because consciousness has an essential property that prevents it from ever being explained. Consequently, philosophical debates over materialism and dualism are a waste of time. Scientific explanations of consciousness fare no better. Scientists do study consciousness, and such investigations will continue to grow and advance. However, none of them will ever reveal what consci.